Radiation-Induced Changes in Microstructure: 13th International Symposium (Part I) 1987
DOI: 10.1520/stp33816s
|View full text |Cite
|
Sign up to set email alerts
|

Void-Precipitate Association During Neutron Irradiation of Austenitic Stainless Steel

Abstract: Microstructural data has recently become available on a single heat of 316 stainless steel irradiated in EBR-II and HFIR, over a wide range of irradiation temperature (55 to 750 C), dose (7 to 75 dpa), and helium generation rate (0.5 to 55 at. ppm He/dpa). dislocation and bubble evolution. Analysis of this data suggests a mechanism which relates to the origin and subsequent growth of precipitate associated voids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Association of large voids with various precipitates (G, η, Laves etc.) [40][41][42][43][44][45] and growth of voids in the compression side of edge dislocations [46,47] is well-known for a long time. Recently, an evidence for the correlations between voids and other defects has been observed by Kozlov, Portnykh et al [48,49] in 20% cold-worked 16Cr-15Ni-2Mo-2Mn austenitic steel irradiated up to ~100 dpa in a BN-600 fast reactor in the temperature range 410 to 600ºC.…”
Section: Discussionmentioning
confidence: 99%
“…Association of large voids with various precipitates (G, η, Laves etc.) [40][41][42][43][44][45] and growth of voids in the compression side of edge dislocations [46,47] is well-known for a long time. Recently, an evidence for the correlations between voids and other defects has been observed by Kozlov, Portnykh et al [48,49] in 20% cold-worked 16Cr-15Ni-2Mo-2Mn austenitic steel irradiated up to ~100 dpa in a BN-600 fast reactor in the temperature range 410 to 600ºC.…”
Section: Discussionmentioning
confidence: 99%
“…[12,[64][65][66][67][68] and growth of voids in the compression side of edge dislocations (see e.g. [62,[69][70]) has been known for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to our knowledge, P segregation on a cavity has only been reported in the case of void-precipitate association during neutron irradiation of austenitic stainless steels. Two types of phosphides Fe2P and Fe3P have been observed to be associated with cavities [59]. From the results of the current study, P was clearly segregating on cavities and was not observed to segregate on other defects neither from EDS nor APT analyses.…”
Section: Discussionmentioning
confidence: 46%